Risk of Pneumonitis Associated With Immune Checkpoint Inhibitors in Melanoma: A Systematic Review and Network Meta-Analysis - Sun, You-Meng; Li, Wei; Chen, Zhi-Yu; Wang, Ying (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitors (ICIs) have dramatically altered the treatment landscape for patients with melanoma. However, their use also generates unique immune-related adverse effects (irAEs). We performed a systematic review and network meta‐analysis to compare the risk of pneumonitis associated with ICIs for patients with advanced or metastatic melanoma. Methods: Phase II/III randomized clinical trials with ICIs were identified through comprehensive searches of multiple databases. An NMA was conducted to compare the risk of pneumonitis associated with ICIs and all‐grade (grade 1‐5) and high‐grade (grade 3‐5) immune‐related pneumonitis (IRP) were estimated by odds ratios (ORs). Results: A total of 10 randomized clinical trials involving 5,335 patients were enrolled in this study. Conventional chemotherapy was associated with a lower risk of grade 1–5 IRP compared with ICIs monotherapy (OR, 0.14, 95% CI, 0.03 to 0.73) and dual ICIs combination (OR, 0.03, 95% CI, 0.00 to 0.19). In addition, dual ICIs combination showed a noticeably higher risk than ICI monotherapy (OR, 4.45, 95% CI, 2.14 to 9.25) of grade 1–5 IRP. No significant difference in grade 1–5 IRP was observed between cytotoxic T lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) inhibitors. As to grade 3‐5 IRP, no statistically significant difference was found among different ICIs-based regimens. Conclusion: These findings revealed that ICIs could increase the risk of all-grade pneumonitis for patients with advanced melanoma, compared with conventional chemotherapy. Dual ICIs combination could further increase the risk of all-grade pneumonitis than ICIs monotherapy. There was no significant difference in the risk of pneumonia between CTLA-4 and PD-1 inhibitors.